Supervision of the financial market in Poland versus protection of consumers - Kudlak, Izabela (Journal of Finance and Financial Law, 2019)
The purpose of this article is to analyze the supervision of the financial market in Poland, comparison of possible concepts and reference this supervision to consumer protection. The author decided to analyze the statement that supervision of the financial market in Poland is a concept that is adequate and does not require changes. The autor wants to check if existing supervision provides consumers with adequate protection. To do so author has analyzed the subject literature and legal acts.